Foreign Tax Credit Pooling System: Is It Always Better? (Part 1 of 3) - KHOO, Teng Aun (Institutional Knowledge at Singapore Management University, 2015)
Presently, there are two systems under which the FTC can be granted subject to satisfying certain conditions 1. FTC source-by-source and country-by-country system (SCS), and 2. FTC pooling system (PS) Under the SCS of computing the FTC, the excess of FTP over the STP on one type of FI (say dividend income) from a foreign country cannot be used to setoff against the excess of STP over the FTP on any other FI. Under the PS, any excess of Foreign Tax Paid (FTP) over the Singapore Tax Payable (STP) on one type of Foreign Income from a foreign country can be setoff against the excess of STP over the FTP on any other FI either from the same or different foreign country. As such it may appear that the PS is better than the SCS. But is it?